Asset Fire Sales and Credit Easing - Shleifer, Andrei; Vishny, Robert W (American Economic Review, 2010)
In a January 2009 lecture on the financial crisis, Federal Reserve Chairman Bernanke advocated a new Fed policy of credit easing, defined as a combination of lending to financial institutions, providing liquidity directly to key credit markets, and buying of long term securities. We show that Bernanke's analysis and recommendations can be naturally considered in a model of "unstable banking," which relies on two mechanisms: 1) fire sales reduce asset prices below fundamental values, and 2) financial institutions prefer speculation to new lending when markets are dislocated. We analyze credit easing and compare it to alternative government interventions during the crisis.